Financial Liberalization, Structural Change, and Real Exchange Rate Appreciations - Meza, Felipe; Urrutia, Carlos (Washington, D.C. : International Monetary Fund, 2010)
We account for the appreciation of the real exchange rate in Mexico between 1988 and 2002 using a two sector dynamic general equilibrium model of a small open economy with two driving forces: (i) differential productivity growth across sectors and (ii) a decline in the cost of borrowing in foreign markets. These two mechanisms account for 60 percent of the decline in the relative price of tradable goods and explain a large fraction of the reallocation of labor across sectors. We do not find a significant role for migration remittances, foreign reserves accumulation, government spending, terms of trade, or import tariffs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet